A context‐aware mobile system for work‐based learning. Issue 2 (21st October 2015) - Zhang, Bingxue; Yin, Chuantao; David, Bertrand; Chalon, René; Xiong, Zhang
ABSTRACT: In this paper, we propose the design, implementation, and evaluation methods and results of a context‐aware mobile system for work‐based learning, named WoBaLearn. The main contribution is we proposed four conceptual design bases which can be applied in developing different work‐based learning environment. With WoBaLearn, professionals can easily access personalized, adaptive and just‐in‐time learning supports through their mobile devices in real working environment. © 2015 Wiley Periodicals, Inc. Comput Appl Eng Educ 24:263–276, 2016; View this article online atwileyonlinelibrary.com/journal/cae ; DOI 10.1002/cae.21704